The value relevance of extent and sophistication of voluntary disclosure. - Foo, Yin Ling. (2008)
This paper examines the value relevance of voluntary disclosure. Disclosure has 3 features: content, sophistication of presentation and quality. We examine the content and sophistication of presentation of 100 Fortune 1000 (U.S) firms. For examining the content or amount of voluntary disclosure made, Form 10K (annual reports filed with SEC) are used instead of the paper annual reports. In the case of content, Form 10K is more informative than the paper annual reports and is readily accessible to investors. Sophistication of presentation entails additional measures to make financial information more visible and accessible. We take levels of Internet disclosure technologies in a firm’s own webpage as a measure of disclosure sophistication. Consistent with Ohlson (1995) and Feltham and Ohlson (1995), we find that book value and return on equity are the main drivers of firm value. However, we also find both content and sophistication of presentation of voluntary disclosures to be associated with firm value.